2016
DOI: 10.1136/injuryprev-2016-042008
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for the Flooring for Injury Prevention (FLIP) Study: a randomised controlled trial in long-term care

Abstract: NCT01618786.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Compliant flooring is a passive intervention approach designed to reduce the stiffness of the ground in order to attenuate the impact forces applied to the body in the event of a fall [ 1 5 ]. It has the potential to reduce the incidence and severity of all fall-related injuries caused by impact to the ground, including hip fractures and traumatic brain injuries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compliant flooring is a passive intervention approach designed to reduce the stiffness of the ground in order to attenuate the impact forces applied to the body in the event of a fall [ 1 5 ]. It has the potential to reduce the incidence and severity of all fall-related injuries caused by impact to the ground, including hip fractures and traumatic brain injuries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compliant flooring has the potential to reduce the incidence and severity of fall-related injuries at all body sites that impact the ground. Furthermore, compliant flooring is a passive intervention, since its effectiveness does not rely on user adherence once it is installed (Lachance, Jurkowski, Dymarz, & Mackey, 2016 ; Wright & Laing, 2012 ).…”
mentioning
confidence: 99%
“…In the LTC setting, stakeholders from health care, research, and industry are involved in making decisions about fall injury prevention strategies, and past research on compliant flooring has engaged stakeholders from each of these sectors (Lachance, Jurkowski, et al., 2016 ; Lachance, Feldman, et al, 2016 ). However, there is limited understanding about stakeholder perceptions of the advantages and disadvantages to implementing compliant flooring and about the research questions that stakeholders deem most important to address in the future.…”
mentioning
confidence: 99%
“…To avoid duplication of effort, we will build on the search already conducted in a scoping review17 which completed its search in May 2016. The clinical12 16 18–26 38–46 and cost-effectiveness11 21 26 40 41 47–63 records identified in the scoping review will be assessed for inclusion in the current review. We will continue the search from May 2016 to present, and will not apply any language restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…A recent scoping review of flooring interventions involved a thorough search of the literature; however, it did not involve a critical appraisal or systematic synthesis 17. A systematic review of studies identified in the scoping review16 18–25 as well as more recent studies,26–31 will provide a more reliable basis for decision-making and identify the next steps for research.…”
Section: Introductionmentioning
confidence: 99%